Uptake of Health Insurance and the Productive Safety Net Program in Rural Ethiopia - Zemzem Shigute; Anagaw Derseh Mebratie; Robert Sparrow; Zelalem Yilma; Getnet Alemu; Arjun S. Bedi (Institute for the Study of Labor (IZA), 2016)
Due to lack of well-developed insurance, credit and labor markets, rural families in Ethiopia are exposed to a range of covariate and idiosyncratic risks. In 2005, to deal with the consequences of covariate risks, the government implemented the Productive Safety Net Program (PSNP) - an active labor market program to build rural assets, and in 2011, to mitigate the financial consequences of ill-health, the government introduced a pilot Community Based Health Insurance (CBHI) Scheme. This paper explores whether scheme uptake and retention is affected by access to the PSNP. Based on several rounds of household level panel data and qualitative information, the analysis shows that participating in the PSNP increases the probability of CBHI uptake by 24 percentage points and enhances scheme retention by 10 percentage points. Analysis of the channels through which the PSNP influences CBHI uptake indicates that the bulk of the effect may be attributed to explicit and implicit pressure applied by government officials on PSNP beneficiaries. Whether this is a desirable approach is debatable. Nevertheless, the results suggest that membership in existing social protection programs may be leveraged to spread new schemes and potentially accelerate poverty reduction efforts.
Keywords: J65; J48; I13; 330; productive safety net program; active labor market program; Ethiopia; community based health insurance; uptake of health insurance